Children of the slaughter : young people of the Holocaust - Gottfried, Ted.; Alcorn, Stephen (Brookfield, Conn.: Twenty-First Century Books, 2001)
Discusses the effects of the Holocaust on more than a million young people.
Includes bibliographical references (p. 108-109) and index.
Wilson's Senior High School, October 2003
Wilson's Junior High School, September 2003
School Library Journal, June 2001
Booklist, May 2001
Voice of Youth Advocates (V.O.Y.A.), April 2002
Keywords: Hitler Youth; Holocaust, 1933-1945.; Holocaust survivors